Domperidone and levodopa in Parkinson's disease. - Shindler, J S (1984)
To study the absorption of levodopa and interaction with the extracerebral dopamine antagonist domperidone, 15 patients with idiopathic Parkinson's disease were given levodopa 500 mg p.o., alone, and with domperidone pre-treatment. Domperidone pretreatment (10, 20, 40 mg, p.o., i.v. or i.m.) caused a mean 12% increase in peak plasma levodopa concentration, which occurred a mean of 10 min earlier than when levodopa was given alone. Parkinsonian disability scores were improved and peak clinical response occurred 16 min earlier with domperidone than without. Domperidone slightly increases the immediate bioavailability (over 4 h) and anti-parkinsonian response to a given dose of levodopa.